2021
DOI: 10.21203/rs.3.rs-480263/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Study on the Adverse Effect of Gel Fracturing Fluid on Gas Sorption Behavior for Illinois Coal

Abstract: Hydraulic fracturing is an effective technology for coal reservoir stimulation. After fracturing operation and flowback, a fraction of fracturing fluid will be essentially remained in the formation which ultimately damages the flowability of the formation. In this study, we quantify the gel-based fracturing fluid induced damages on gas sorption for Illinois coal in US. We conducted the high-pressure methane and CO2 sorption experiments to investigate the sorption damage due to the gel residue. The infrared spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Huang Qiming used 13 C NMR experiments and combined them with ACD Labs software to optimize the construction of the molecular structure model of a coal sample from the Illinois Basin, USA. This coal sample belongs to the high-rank coal, and we compared the waveform diagram of the mapped coal sample with the waveform diagram obtained from the actual NMR experiments, both of which are in good agreement, and concluded that the mapped coal molecular structure is consistent with the structure of coal in the real coal seam . In this paper, the molecular structure of Illinois Basin coal constructed by Huang Qiming was used for molecular simulation studies.…”
Section: Resultsmentioning
confidence: 68%
“…Huang Qiming used 13 C NMR experiments and combined them with ACD Labs software to optimize the construction of the molecular structure model of a coal sample from the Illinois Basin, USA. This coal sample belongs to the high-rank coal, and we compared the waveform diagram of the mapped coal sample with the waveform diagram obtained from the actual NMR experiments, both of which are in good agreement, and concluded that the mapped coal molecular structure is consistent with the structure of coal in the real coal seam . In this paper, the molecular structure of Illinois Basin coal constructed by Huang Qiming was used for molecular simulation studies.…”
Section: Resultsmentioning
confidence: 68%
“…In recent years, with the further study of expansive rock and soil from macro to micro, the specific surface area has been more focused [49,[58][59][60][61][62][63][64][65][66], which can reflect the expansion characteristics and expansion potential of expansive rock and soil. At present, there are many studies on the specific surface area of expansive soil [49,58,59,63,67,68], while there are few studies on expansive rocks [60], especially the specific surface area of the first type of expansive rocks.…”
Section: Ultimate Expansion Forcementioning
confidence: 99%
“…The isothermal adsorption experiments targeted at the organic‐rich coal from different formations are commonly used to investigate the methane adsorption behavior on coal, which reveals the influences of various factors on the methane adsorption capacity, including gas pressure, 8,9 temperature, 10 moisture, 11,12 organic matter, 13 clay minerals, 8 pore structure, 14,15 and fracturing fluid, 16,17 and so forth. The pressure and temperature of CBM reservoirs are both increased with the increased depth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is significant to understand the adsorption characteristics of methane on coal not only for CBM resource evaluation and productivity prediction but also for evaluating the potential severity of gas disasters in new mines or in unmined areas of existing mines. 7 The isothermal adsorption experiments targeted at the organic-rich coal from different formations are commonly used to investigate the methane adsorption behavior on coal, which reveals the influences of various factors on the methane adsorption capacity, including gas pressure, 8,9 temperature, 10 moisture, 11,12 organic matter, 13 clay minerals, 8 pore structure, 14,15 and fracturing fluid, 16,17 and so forth. The pressure and temperature of CBM reservoirs are both increased with the increased depth.…”
mentioning
confidence: 99%